Penyusunan Alat Ukur Kesiapan Menghadapi Kematian dalam Perspektif Islam - Azahra, Fathia Fitri; Arsita, Dina; Ruhaena, Lisnawati; Aulia, Ranisya Wilda; Purwandari, Eny; Fitri, Rindifa Amilatul (UIN Sunan Kalijaga, 2025)
This study aims to develop a valid and reliable instrument to measure preparedness for death from an Islamic perspective. This measurement tool is essential for Muslim communities as it incorporates Islamic religious values. The research was conducted in three stages: literature review, semi-structured interviews, and blueprint development. The collected data were analyzed using Exploratory Factor Analysis (EFA) to examine the factor structure and construct validity of the instrument. The initial blueprint consisted of 55 items, which were reduced to 20 items after content validity assessment by seven experts (three Islamic scholars and four psychologists). The instrument was administered to 205 respondents. The EFA results refined the scale from four factors and 20 items to two factors and 19 items. The findings indicate that preparedness for death in Islam comprises two dimensions: a transcendental dimension (belief in destiny, awareness of the afterlife, and commitment to worship) and a social dimension (support from family, peers, and the religious environment). Penelitian ini bertujuan menyusun instrumen yang valid dan reliabel untuk mengukur kesiapan menghadapi kematian dalam perspektif Islam. Alat ukur ini penting untuk masyarakat muslim karena mempertimbangkan aspek religius Islam. Penelitian dilakukan dalam tiga tahap: kajian literatur, wawancara semi-terstruktur, serta penyusunan blueprint. Data yang terkumpul dianalisis menggunakan teknik Exploratory Factor Analysis (EFA) guna mengeksplorasi struktur faktor dan menguji konstruksi alat ukur yang dikembangkan. Blueprint yang awalnya berjumlah 55 aitem menjadi 20 aitem setelah uji validitas isi oleh tujuh ahli (3 ahli agama dan 4 ahli psikologi). Responden yang mengisi skala ini adalah 205 orang. Dalam proses EFA empat faktor dan 20 aitem mengerucut menjadi dua faktor dan 19 aitem. Hasil penelitian Temuan menunjukkan bahwa kesiapan menghadapi kematian dalam Islam terdiri dari dimensi transendental (iman kepada takdir, kesadaran akan kehidupan setelah mati, dan komitmen ibadah) serta dimensi sosial (dukungan keluarga, teman, dan lingkungan religius)